Endoscopic ultrasound-guided tissue sampling: European Society of Gastrointestinal Endoscopy (ESGE) Technical and Technology Review - Facciorusso, Antonio; Arvanitakis, Marianna; Crinò, Stefano Francesco; Fabbri, Carlo; Fornelli, Adele; Leeds, John; Archibugi, Livia; Carrara, Silvia; Dhar, Jahnvi; Gkolfakis, Paraskevas; Haugk, Beate; Iglesias Garcia, Julio; Napoleon, Bertrand; Papanikolaou, Ioannis S.; Seicean, Andrada; Stassen, Pauline M. C.; Vilmann, Peter; Tham, Tony C.; Fuccio, Lorenzo (Endoscopy, 2025)
This Technical and Technology Review from the European Society of Gastrointestinal Endoscopy (ESGE) represents an update of the previous document on the technical aspects of endoscopic ultrasound (EUS)-guided sampling in gastroenterology, including the available types of needle, technical aspects of tissue sampling, new devices, and specimen handling and processing. Among the most important new recommendations are:ESGE recommends end-cutting fine-needle biopsy (FNB) needles over reverse-bevel FNB or fine-needle aspiration (FNA) needles for tissue sampling of solid pancreatic lesions; FNA may still have a role when rapid on-site evaluation (ROSE) is available.ESGE recommends EUS-FNB or mucosal incision-assisted biopsy (MIAB) equally for tissue sampling of subepithelial lesions ≥20 mm in size. MIAB could represent the first choice for smaller lesions (<20 mm) if proper expertise is available.ESGE does not recommend the use of antibiotic prophylaxis before EUS-guided tissue sampling of solid masses and EUS-FNA of pancreatic cystic lesions.